2012
DOI: 10.1007/s10803-012-1464-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Finnish Autism Spectrum Screening Questionnaire (ASSQ) for Clinical Settings and Total Population Screening

Abstract: We assessed the validity and determined cut-off scores for the Finnish Autism Spectrum Screening Questionnaire (ASSQ). A population sample of 8-year-old children (n = 4,408) was rated via the ASSQ by parents and/or teachers, and a subgroup of 104 children was examined via structured interview, semi-structured observation, IQ measurement, school observation, and medical records. Autism spectrum disorders (ASDs) were diagnosed following DSM-IV-TR criteria. A search for hospital-registered ASDs was performed. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 23 publications
1
41
0
1
Order By: Relevance
“…During the validation process of the ASSQ we found that the screening ability of the parent rated ASSQ differed substantially from that in other cultures and countries (Mattila et al, 2012). Since ASD is a neurobiological disorder, the expression of its core symptoms is not likely to be culturally determined.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…During the validation process of the ASSQ we found that the screening ability of the parent rated ASSQ differed substantially from that in other cultures and countries (Mattila et al, 2012). Since ASD is a neurobiological disorder, the expression of its core symptoms is not likely to be culturally determined.…”
mentioning
confidence: 94%
“…Of the ASD screening scales designed for school aged children, only the Autism Spectrum Screening Questionnaire (ASSQ) has been properly validated in Finland (Mattila, Jussila, & Linna, et al, 2012). During the validation process of the ASSQ we found that the screening ability of the parent rated ASSQ differed substantially from that in other cultures and countries (Mattila et al, 2012).…”
mentioning
confidence: 99%
“…The ASSQ (20,21) is a 27-item parent or teacher-report inventory that is designed to screen for ASD in children with full-scale intelligence quotient ≥50). Of the ASD screening measures, the ASSQ is the only questionnaire that has been validated for Finland (24). The ASSQ covers the main areas of ASD (i.e., social interaction, communication, and restricted and repetitive behaviors) as well as motor deficits and behaviors (e.g., clumsiness) and other associated symptoms (e.g., motor and vocal tics).…”
Section: Methodsmentioning
confidence: 99%
“…Families of 88 students participated (82 families in total; six children were siblings from the same families). Controls were screened with the ASSQ, and those exceeding 7 points were excluded (24). We subsequently checked all potential participants' hospital records to ensure that none of the control children were ASD outpatients of Oulu University Hospital.…”
Section: Participantsmentioning
confidence: 99%
“…Araştırmacılar TIQ≥50 olan olguları 'iş-levselliği daha iyi/yüksek olan olgular-higher functioning' olarak tanımlamaktadır (Mattila ve ark. 2009, Mattila ve ark. 2012.…”
Section: öRneklem Ve Uygulamaunclassified